Faktor-faktor yang Mempengaruhi Kinerja Keuangan terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2023 - Nurwahyuni Syahrir; Nur Fitriayu Mandasari; Abdul Galib; Farhan Anis (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to determine the effect of financial performance as measured using the financial ratios Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), Loan to Deposit Ratio (LDR) and Operating Expenses to Operating Income (BOPO) on stock prices in banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2023. The population in this study were all banking companies listed on the Indonesia Stock Exchange in 2017-2023. The sample consisted of 15 companies using the purposive sampling method. The type of data used is secondary data obtained from the financial statements of each company. This study uses linear regression analysis techniques with the SPSS program. The data analysis used is the Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothesis testing through partial test (t-test), simultaneous test (F-test), and determination coefficient test. The results of this study indicate that partial Return On Assets (ROA) has a positive and significant effect on stock prices, Return On Equity (ROE) has a negative and insignificant effect on stock prices, Debt to Equity Ratio (DER) has a positive and insignificant effect on stock prices, Loan to Deposit Ratio (LDR) has a negative and insignificant effect on stock prices, and Operating Expenses to Operating Income (BOPO) has a negative and significant effect on stock prices in banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2023.